Contingent Democrats in Action: Organized Labor and Regime Change in the Republic of Niger - Sebastian Elischer (German Institute of Global and Area Studies (GIGA), 2013)
The effects of organized labor on regime change in developing countries are not clear-cut. Optimists argue that union agitation is conducive to both democratic transition and consolidation processes. Pessimists hold that unions will support any regime that is conducive to their demands. Accordingly, unions may support regime transitions; however, once their economic interests are under threat, they will jeopardize the subsequent consolidation process. Systematic studies on the effects of organized labor on regime change in sub-Saharan Africa are sparse and largely confined to the (pre)transition phase. This article examines the role of organized labor in Niger between 1990 and 2010. Given the high number of regime breakdowns during the period, a longitudinal study of Nigerien labor enables a critical examination of motives and actions of organized labor toward different regime types. In contrast to other recent findings on African unionism, the article confirms the pessimistic view.
Keywords: 300; political science; democratization; sub-Saharan Africa; trade unions; Niger; civil society; francophone Africa